Early versus Traditional Oral Feeding after Elective Intestinal Stoma Closure (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Postoperative feeding protocols following elective intestinal stoma closure remain debated, with limited consensus on optimal timing. Early enteral feeding is hypothesized to enhance recovery, reduce complications, and lower healthcare costs, particularly in resource-limited settings. The study aimed to compare the morbidity and outcome of early versus traditional oral feeding after elective intestinal stoma closure. Materials and methods: This quasi-experimental study compared the outcomes of early oral feeding (Within 12–24 hours post-surgery) versus traditional feeding (Initiated after ileus resolution) in 88 patients undergoing elective intestinal stoma closure (Ileostomy/colostomy) in the Department of Surgery, Chittagong Medical College Hospital from January 2022 to December 2022. Patients were divided into Group A (Traditional feeding, n=44) and Group B (Early feeding, n=44). Postoperative outcomes included bowel function recovery, complications (Fever, cough, wound infection, anastomotic leakage) and hospital stay. Results: Group B had significantly lower postoperative complications on days 3, 5 and 7. By day 3, Group A had higher rates of fever (61.4% vs. 20.5%) wound infection (25% vs. 9.1%), and cough (65.9% vs. 31.8%), all statistically significant (p